Physical Education Teachers’ Relationship with University as Scientific, Educational and Social Institution (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Academic environment necessitates university teachers to carry out three essential  professional  functions:  scientific,  educational  and  social,  and  to  gain  such  professional  self-perception which is desirable for the individuals themselves and are also rooted in the cultural perception of the academic community and matches the expectations of modern society. Research aim was to reveal the relationship between university physical education teachers and the university as scientific, educational and social institution.Research  methods.  The  study  employed  a  non-standardized  questionnaire  drawing  upon  the  survey  of L. Paterson et al. (2003) about the expression of democratic intellect in Scotland and England. The attitudes of the research participants were interpreted using nonparametric statistical methods.Research results. Educational activities remained the major priority of professional activities at the beginning of professional careers. The lower priority was ascribed to scientific and social functions.Discussion  and  conclusions.  Physical  education  teachers  carried  out  three  essential  professional  functions: scientific, educational and social giving the major priority to the educational function: preparation of textbooks, course books, worksheets, courses, vocational events, updating their professional knowledge. Physical education teachers are also oriented towards applied research which is related to scientific function at the university – preparation of doctors of science.Keywords: higher education, academic profile, professional functions of teachers.